2023
DOI: 10.1001/jamainternmed.2022.5472
|View full text |Cite
|
Sign up to set email alerts
|

Association of Pneumococcal Conjugate Vaccine Use With Hospitalized Pneumonia in Medicare Beneficiaries 65 Years or Older With and Without Medical Conditions, 2014 to 2017

Abstract: ImportanceThe association of 13-valent pneumococcal conjugate vaccine (PCV13) use with pneumonia hospitalization in older adults, especially those with underlying medical conditions, is not well described.ObjectiveTo evaluate the association of PCV13 use with pneumonia, non–health care–associated (non-HA) pneumonia, and lobar pneumonia (LP) hospitalization among US Medicare beneficiaries 65 years or older.Design, Setting, and ParticipantsThis cohort study with time-varying exposure assignment analyzed claims d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

2
25
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 16 publications
(28 citation statements)
references
References 23 publications
2
25
1
Order By: Relevance
“…Unlike earlier US studies, Kobayashi et al included approximately half of all US adults 65 years or older across all 50 states and DC and was representative of the US population. Importantly, it also included many adults with chronic medical conditions, which allowed the authors to separately evaluate vaccine effectiveness in low-risk and high-risk adults.…”
supporting
confidence: 81%
See 4 more Smart Citations
“…Unlike earlier US studies, Kobayashi et al included approximately half of all US adults 65 years or older across all 50 states and DC and was representative of the US population. Importantly, it also included many adults with chronic medical conditions, which allowed the authors to separately evaluate vaccine effectiveness in low-risk and high-risk adults.…”
supporting
confidence: 81%
“…Given surveillance data from 2014 to 2017 showing that PCV13 had a limited association with further reducing PCV13-type invasive pneumococcal disease (IPD), the ACIP subsequently voted in 2019 to remove this routine recommendation . However, several recent analyses have found that PCV13 use in older US adults also protects against a broader set of respiratory infections beyond vaccine-type IPD, such as all-cause pneumonia . Whether reductions in all-cause pneumonia among older persons is similar across underlying medical conditions is not known.…”
mentioning
confidence: 99%
See 3 more Smart Citations